Efficacy of Simethicone in Preparation Prior to Upper Gastrointestinal En-doscopy - Majid Ahsan; Leila Babaei; Ali Gholamrezaei; Mohammad Hassan Emami (مجله دانشکده پزشکی اصفهان, 2011)
Background: The presence of foam/bubbles in stomach and duodenum is a common problem during esophagogastroduodenoscopy (EGD) that interferes with precise evaluation of the mucosa. We evaluated the effectiveness of simethicone in reducing foam/bubbles in stomach and duodenum, endoscopy duration, and patient satisfaction. Methods: This double-blind, randomized, placebo-controlled trial was conducted on candidates for elective EGD referring to Poursina Hakim Clinic, Isfahan (Iran). Participants received 40 mg chewable tablet of simethicone or placebo, with 30 ml water, 15-30 minutes before the EGD. Foam/bubbles during endoscopy were assessed and graded by a single endoscopist from 0 to 3 and the endoscopy duration was recorded. Patient’s satisfaction was scored from 0 to 10. Finding: During the study, 90 and 83 patients were entered into the simethicone and placebo groups, respectively. Degree of foam/bubbles was significantly less in simethicone compared to placebo group (P = 0.002). No difference was found between the two groups in foam/bubbles of duodenum (P > 0.05). Duration of endoscopy was, on average, one minute shorter in simethicone compared with placebo group (P < 0.001). Patient’s satisfaction was similar between the two groups. No adverse effect was observed from simethicone. Conclusion: Simethicone before EGD significantly reduce the foam/bubbles in stomach and provide better visibility for evaluating the mucosa, and also decrease the duration of endoscopy. Accordingly, routine administration of simethicone for preparation before EGD is recommended.